2002
DOI: 10.1016/s0002-9440(10)61170-4
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Up-Regulation of Vascular Endothelial Growth Factor Expression in Murine Macrophages by Adenosine A2A Receptor Agonists and Endotoxin

Abstract: Under normoxic conditions, macrophages from C57BL mice produce low levels of vascular endothelial growth factor (VEGF). Hypoxia stimulates VEGF expression by approximately 500%; interferon-gamma (IFN-gamma) with endotoxin [lipopolysaccharide (LPS)] also stimulates VEGF expression by approximately 50 to 150% in an inducible nitric oxide synthase (iNOS)-dependent manner. Treatment of normoxic macrophages with 5'-N-ethyl-carboxamido-adenosine (NECA), a nonselective adenosine A(2) receptor agonist, or with 2-[p-(2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
134
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 184 publications
(146 citation statements)
references
References 53 publications
9
134
0
3
Order By: Relevance
“…Adenosine, acting at its receptors, promotes granulation tissue formation both directly and indirectly [14][15][16]. It has been shown that A 1 R and A 2A R hasten the resolution of acute inflammation by a variety of mechanisms [17][18][19].…”
Section: The Role Of Adenosine and Its Receptors In Granulation Tissumentioning
confidence: 99%
See 1 more Smart Citation
“…Adenosine, acting at its receptors, promotes granulation tissue formation both directly and indirectly [14][15][16]. It has been shown that A 1 R and A 2A R hasten the resolution of acute inflammation by a variety of mechanisms [17][18][19].…”
Section: The Role Of Adenosine and Its Receptors In Granulation Tissumentioning
confidence: 99%
“…Stimulation of A 2A R and A 2B R directly stimulates endothelial cell proliferation and A 2A R stimulation leads to tube formation in vitro. Moreover, A 2B R occupancy upregulates VEGF, bFGF, and Il-8 in human endothelial cells via G q and possibly G 12/13 and activation of phospholipase C. A 2A R also upregulates VEGF in macrophages in a PKA-independent mechanism [14,15]. Additionally, A 2A receptor stimulation suppresses thrombospondin-1 expression in microvascular endothelial cells, and thrombospondin-1 suppresses angiogenesis in vitro in microvascular endothelial cells [20] although others have reported that A 2A and A 2B receptor stimulation promotes angiogenesis through increased macrophage expression of thrombospondin-1 [21].…”
Section: The Role Of Adenosine and Its Receptors In Granulation Tissumentioning
confidence: 99%
“…This synergistic up-regulation is independent of hypoxia, NO, and protein kinase-A and is stronger than that induced by hypoxia alone. 3 Mammalian toll-like receptors (TLRs) are members of a family of proteins that resemble the Drosophila toll protein. 4,5 Toll plays a role in dorsal-ventral patterning in the developing fly embryo, and also plays a key role in regulating the innate immune response of adult flies to fungi.…”
Section: Adenosine a 2a Receptor (A 2a R) Agonists Synergize With Escmentioning
confidence: 99%
“…For the synthesis of PAM 3 Cys and PAM 3 CAG, reagents were purchased from Alfa Aesar (Ward Hill, MA) or Aldrich (Milwaukee, WI). N-Fmoc-protected alanine and the preloaded Wang resin were from NovaBiochem (Darmstad, Germany).…”
Section: Synthesis Of Pam 3 Cys and Pam 3 Cagmentioning
confidence: 99%
“…Adenosine increases the VEGF release from macrophages, thus facilitating the process of angiogenesis [103]. Adenosine and LPS via A 2A receptors and toll-like receptor 4 (TLR4) synergistically upregulate the production of VEGF by macrophages in hypoxia-and NOindependent manner [104].…”
Section: Adenosine and Macrophage Interaction In Tumor Microenvironmentmentioning
confidence: 99%